A DNA nanoribbon as a potent inhibitor of metallo-β-lactamases. Issue 63 (24th July 2017) - Ouyang, Xiangyuan; Chang, Ya-Nan; Yang, Ke-Wu; Wang, Wen-Ming; Bai, Jian-Jian; Wang, Jian-Wei; Zhang, Yue-Juan; Wang, Si-Yao; Xie, Bin-Bin; Wang, Li-Li
Abstract : A DNA nanoribbon has been discovered that inhibits the activity of metallo-β-lactamases by binding to the enzyme. Abstract : We discovered a promising metallo-β-lactamase inhibitor, a DNA nanoribbon, by enzymatic kinetics and isothermal titration calorimetry evaluations. Atomic force microscopy, gel electrophoresis, competitive binding experiments, circular dichroic and thermal denaturation studies suggested that the DNA nanoribbon could bind to the enzyme through a minor groove.